Is postoperative radiotherapy effective in patients with completely resected pathologic stage IIIA(N2) non-small cell lung cancer? High-risk populations should consider it - Shu-Xian Zhang; Chen-Chen Zhang; Run-Ping Hou; Xu-Wei Cai; Jun Liu; Wen Yu; Qin Zhang; Jin-Dong Guo; Chang-Lu Wang; Hong-Xuan Li; Zheng-Fei Zhu; Xiao-Long Fu; et al. (Clinical and Translational Radiation Oncology)
Background and purpose: We aimed to assess the benefits of postoperative radiotherapy (PORT) in completely resected patients with pathologic stage IIIA(N2) non-small cell lung cancer (NSCLC) with a high risk of locoregional recurrence (LRR). Materials and methods: A prospective, randomized trial was conducted starting in July 2016 to explore the optimal timing of PORT in high-LRR-risk patients with completely resected IIIA(N2) NSCLC (NCT02974426). Patients were identified as high-LRR-risk patients via the prognostic index (PI) model and were randomly assigned to PORT-first or PORT-last treatment. To evaluate PORT for high-LRR-risk patients, all patients in this trial constituted the PORT cohort, whereas high-LRR-risk patients without PORT were selected from a retrospective cohort as the non-PORT cohort. Propensity score-matched (PSM) analyses were conducted to compare overall survival (OS), disease-free survival (DFS), locoregional recurrence-free survival (LRFS) and distant metastasis-free survival (DMFS). Results: Between 2016 and 2022, 132 patients were included in the trial, with a median follow-up of 49.3 months. The 3-year OS rate was 83.2 %, and the 3-year DFS rate was 35.0 %. Among these patients, 122 patients (92 %) received planned PORT. For 132 intention-to-treat patients, PSM analysis with the non-PORT cohort (n = 307) resulted in 130 matched pairs. The results revealed that PORT improved LRFS (3-year LRFS, 77.6 % vs. 57.3 %; p = 0.00014), DFS (3-year DFS, 35.2 % vs. 28.6 %; p = 0.038), and OS (3-year OS, 83.0 % vs. 60.7 %; p = 0.00017), with no difference in DMFS (p = 0.17). Conclusion: PORT could increase local control, DFS, and OS in high-LRR-risk patients with completely resected IIIA(N2) NSCLC. Future research should utilize multidimensional data to pinpoint more precise subgroups benefiting from PORT, with prospective trials validating these findings.